MANAJEMEN KEGAWATDARURATAN TERTELAN BUR (STUDI KASUS) - fitri isnaini (Universitas Baiturrahmah, 2020)
Introduction: Emergency conditions of ingestion of foreign objects in dental practice may occasionally occur, one of which is ingestion of burs. In most cases, the foreign object passes through the digestive tract without difficulty, but some may require surgery. Immediate removal of the object may be necessary because long-term retention leads to complications and even death. Case and Management: 21 years old man underwent dental procedures, five minutes after preparation, the bur came off and then swallowed. The patient is referred to the radiology and nutrition department, given antipyretic, anti-inflammatory, laxatives, electrolyte fluids, high-fiber foods, multiply water. The bur is eliminated from the body after 4 days. Conclusion: Dentists and dental therapists should have the skills in emergency management of bur ingestion. Things that need to be considered to prevent the emergency are pre-action preparation (area isolation and double-check of the instruments), effective communication between patient and doctors (delivering instructions in case of emergency), informed consent, good coordination and preparedness between medical staff include radiology, nutrition, and nurses.